Digital Transformation of Arabic Learning Environments in Islamic Higher Education - Imelda Wahyuni; Abdul Azis; Nurul Afiyah; Audi Aqshal Afandi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Rapid digitalization has expanded opportunities for language learning in higher education, however, Arabic learning in Islamic higher education often remains fragmented, lecturer-centred, and weakly supported by institutional policy, limiting its effectiveness and sustainability. This study investigates how digitalization restructures Arabic language learning environments and identifies factors influencing their coherence and long-term development. Using a qualitative interpretive-exploratory multi-site design, the research was conducted at five Islamic higher education institutions in Southeast Sulawesi, Indonesia. Data were collected through classroom observations, in-depth interviews, focus group discussions, and document analysis involving lecturers, students, and institutional stakeholders. The data were analyzed through iterative coding, thematic interpretation, and contextual synthesis. The findings indicate that in formal settings, digitalization mainly functions as a supplementary tool that improves access to learning resources and Arabic input, but has not substantially transformed classroom interaction or pedagogy. In contrast, informal digital environments, particularly student-led and community-based platforms, extend language exposure and foster learner autonomy, although they remain fragmented and weakly institutionalized. Leadership commitment, infrastructure readiness, and digital literacy emerged as key factors shaping sustainability. The study concludes that digitalization should be understood as an environmental transformation rather than mere technology adoption. It recommends that Islamic higher education institutions develop integrated digital learning ecosystems through curriculum reform, staff development, governance support, and active student participation.